Preliminary Safety Evaluation and Biochemical Efficacy of a Carum carvi Extract: Results from a Randomized, Triple‐Blind, and Placebo‐Controlled Clinical Trial. (17th March 2014) - Kazemipoor, Mahnaz; Radzi, Che Wan Jasimah Bt Wan Mohamed; Hajifaraji, Majid; Cordell, Geoffrey A.
<x xml:space="preserve">Abstract</x> Carum carvi L. (Apiaceae) is known as caraway, and its derivatives find wide medicinal use for health purposes, including for gastrointestinal problems and obesity. Since there is inconsistency among the reports on the safety of this plant in humans, this research was aimed at assessing the safety of a characterized caraway aqueous extract (CAE) in a randomized, triple‐blind, placebo‐controlled study. Seventy, overweight and obese, healthy women were randomly assigned into placebo (n = 35) and plant extract (n = 35) groups. Participants received either 30 ml/day of CAE or placebo. Subjects were examined at baseline and after 12 weeks for changes in heart rate, blood pressure, urine test, 25‐item blood chemistries, and general health status. No significant changes of blood pressure, heart rate, urine specific gravity, and serum blood tests were observed between the two groups before and after treatment. However, in the complete blood count test, red blood cell levels were significantly (p < 0.01) increased, and platelet distribution width was significantly decreased after the dietary CAE treatment, as compared with placebo. No negative changes were observed in the general health status of the two groups. This preliminary study suggests that the oral intake of CAE appears to be without any adverse effects at a dosage of 30 ml daily for a period of 12 weeks. Copyright © 2014 John Wiley & Sons, Ltd.